Protective role of Ficus deltoidea against BPA-induced impairments of the follicular development, estrous cycle, gonadotropin and sex steroid hormones level of prepubertal rats - Mohamad Zaid, Siti Sarah; Othman, Shatrah; M. Kassim, Normadiah (BMC, 2018)
Ficus deltoideais one of the well-known medicinal plants in Malaysia that is traditionally used by the Malay community totreat various ailments and for maintenance of female reproductive health. The objective of this study is to evaluate thepotential protective roles ofFicus deltoideaagainst BPA-induced toxicity of the pituitary-ovarian axis in pre-pubertal femalerats. In this study, four groups of pre-pubertal female Sprague Dawley rats were administered with the followings by oralgavage for a period of six weeks: NC (negative control- treated with vehicle), PC (positive control-treated with BPA at 10 mg/kg/BW), F (treated withFicus deltoideaat 100 mg/kg/BW, then exposed to BPA at 10 mg/kg/BW) and FC (Ficus deltoideacontrol - treated withFicus deltoideaat 100 mg/kg/BW). Daily vaginal smear, ovarian follicular development as well asgonadotropin and sexual-steroid hormone levels were determined. The findings showed thatFicus deltoideademonstratedpreventive role against BPA-induced toxicity on the ovaries. This was evident bythe increased percentage of rats withnormal estrous cycle, qualitatively reduced number of atretic follicles (as observed in histopathological examination) andnormalization of the gonadotropins hormone (FSH) and sexual steroid hormone (progesterone) levels. In conclusion,Ficusdeltoideahas the capability to prevent the effects of BPA toxicity in the hypothalamus-pituitary-gonadal axis of prepubertalfemale reproductive system, possibly due to its variety ofphytochemical properties. Therefore, these findingsstrongly support the traditional belief that this medicinal plant is beneficial as daily dietary supplement forthe maintenance of female reproductive health.